2021
DOI: 10.5222/gju.2021.79188
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Retroperitoneal Hemorrhage: Same Complication, Two Different Types of Treatment

Abstract: One of the reasons for the high mortality in COVID-19 patients is the increased risk of disseminated intravascular coagulation (DIC) and venous thromboembolism. For this reason, the use of anticoagulant treatments has become widespread. One of the rare complications of anticoagulant therapy is retroperitoneal hemorrhage. These hemorrhagies require immediate intervention. Retroperitoneal hemorrhage should be kept in mind among the many complications that develop in the patient who was followed up during the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The most important cause of death in COVID-19 patients is thromboembolism due to the cytokine storm and altered coagulation profiles of the patients [1,8,9]. To avoid this complication, the authors have recommended anticoagulation treatment [10,11]. However, there is no standard dose that can provide a totally safe environment for patients because the clinic of each patient is unique, and the predisposition to this complication may vary [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…The most important cause of death in COVID-19 patients is thromboembolism due to the cytokine storm and altered coagulation profiles of the patients [1,8,9]. To avoid this complication, the authors have recommended anticoagulation treatment [10,11]. However, there is no standard dose that can provide a totally safe environment for patients because the clinic of each patient is unique, and the predisposition to this complication may vary [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…In the pathophysiology of COVID‐19, there is a cytokine storm caused by hyperinflammation and immunosuppression and the resulting microthrombosis and disseminated intravascular coagulation (DIC) development (Jose & Manuel, 2020 ; Tay et al, 2020 ). Although the lungs are the first and most affected organs by this cytokine storm, studies have shown that the whole body, especially the cardiovascular system, is affected due to bleeding and coagulation at multiple levels such as endothelial damage, microangiopathy and vasculitis (Aydın Yoldemir et al, 2021 ; Menter et al, 2020 ). Studies have shown that endothelial dysfunction, subclinical hypogonadism, anxiety and impaired cardiac and pulmonary haemodynamics may develop with COVID‐19, which may contribute to the emergence of ED (Kresch et al, 2021 ; Sansone et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%